1995
DOI: 10.1172/jci117697
|View full text |Cite
|
Sign up to set email alerts
|

The cutaneous T cell lymphoma, mycosis fungoides, is a human T cell lymphotropic virus-associated disease. A study of 50 patients.

Abstract: For nearly two decades it has been suspected that the cutaneous T cell lymphoma, mycosis fungoides (MF), and its leukemic variant, the Sezary syndrome, are caused by the human T lymphotropic virus (HTLV-I/ll). Arguments against this concept included the finding that only a small number of MF patients have antibodies to HTLV-I/ll and that attempts to detect proviral sequences by mere Southern hybridization of extracted DNA usually met with failure. However, we have reported repeatedly that HTLV-like particles e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(85 citation statements)
references
References 54 publications
3
79
1
2
Order By: Relevance
“…HTLV-1 is found in adult T-cell lymphoma and leukemia, and it has been implicated by several studies in CTCL (Zucker-Franklin and Pancake, 1994;Pancake et al, 1995;Khan et al, 1996). However, others have not been able to confirm these findings (Boni et al, 1996;Wood et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HTLV-1 is found in adult T-cell lymphoma and leukemia, and it has been implicated by several studies in CTCL (Zucker-Franklin and Pancake, 1994;Pancake et al, 1995;Khan et al, 1996). However, others have not been able to confirm these findings (Boni et al, 1996;Wood et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Although viruses are known to provide chronic immune stimulation, the findings of their association with MF are controversial (Pancake et al, 1995;Boni et al, 1996;Nagore et al, 2000;Herne et al, 2003). HTLV-1 is found in adult T-cell lymphoma and leukemia, and it has been implicated by several studies in CTCL (Zucker-Franklin and Pancake, 1994;Pancake et al, 1995;Khan et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This cellular background was chosen because ATLL is an aging-related malignancy requiring clinical latency periods of 25 to 40 years prior to disease onset (29), which suggests that genetic mutations linked to the aging process likely contribute to leukemogenesis. Werner's syndrome is a premature aging disorder (45) that mimics or recapitulates many of the clinical and cellular features of normal aging, and WRN locus (8p11-12) mutations have been found in HTLV-1-infected ATLL patient lymphocytes and in HTLV-1-infected mycosis fungoides/Sezary syndrome cells (4,30,53,69,82). Neither c-Myc nor HTLV-1 p30 II (HA) alone significantly induces focus formation in immortalized human WRN Ϫ/Ϫ fibroblasts (Fig.…”
Section: Htlv-1 P30mentioning
confidence: 99%
“…Most patients with CTCL are negative for antibodies to the structural proteins of HTLV-I, and thus a causative role for this virus is usually dismissed. However, numerous studies have found HTLV-I-related proviral tax sequence or deleted proviruses in tumor samples from CTCL patients [27][28][29][30][31][32][33][34]. Recently a study on the northeastern coast of Brazil found HTLV-I integrated proviral sequences by southern blot in several mycosis fungoides-like cutaneous lymphomas, and CD30 + largecell anaplastic lymphomas [35].…”
Section: Htlv-i-associated Cutaneous T-cell Lymphoma (Ctcl)mentioning
confidence: 99%